Development Of Particle Image Velocimeter For Two-Dimensional (2d) Flow Field Measurement - Fahizan, Mahmud (Universiti Malaysia Sarawak (UNIMAS), 2018)
Fluid flow field measurement is crucial for greater understanding of fluid flow behaviour in numerous application such as in biomedical, aerodynamics, aquatics, machinery and combustion. Particle image velocimetry (PIV) is a non-intrusive measurement technique that capable of quantifying instantaneous flow field media. This particular measurement system can provide insightful and detailed information of the flow field by tracking the motion of seeding particles, as these particles are believed to be neutrally buoyant and faithfully follow the dynamics of fluid. This measurement technique is considered a step higher compared to intrusive measurement as it does not make contact with the fluid flow system. Therefore, the aim of this project is to develop a particle image velocimeter (PIV) system that can measure two-dimensional fluid flow. A low cost PIV system was developed comprises of light source (preferably coherent), recording hardware, seeding particles and analysis software for image processing. The falling sphere experiment was conducted to demonstrate the PIV system. Results of the experiment were compared and good agreement with theory and CFD simulation are achieved.